Compositional dependence of electrical conduction in solution grown Zn1-xCrxSe thin films: a correlation - Deshmukh, S. L.; Pingale, P. C.; Chavan, G. T.; Pawar, S. T.; Prakshale, V. M.; Kamble, S. S.; Jadkar, S. R.; Chaure, N. B.; Gopinath, C. S.; Maldar, N. N.; Deshmukh, L. P. (Journal of Materials Science: Materials in Electronics, 2017)
Zinc selenide (ZnSe) has a typical band gap of 2.7 eV suitable for window application and can easily be synthesized using a liquid phase chemical bath deposition. An attempt is made to tune its band gap and other characteristics to cope with a maxima of the solar spectrum by deliberate addition of Cr3+. ZnSe and Zn1-xCrxSe (0 <= x <= 0.35) thin films were obtained under the controlled deposition conditions (temperature = 70 A degrees C, time = 210 min, pH = 10, etc). The compositional analysis showed Zn2+ replacement by Cr3+. The X-ray photoelectron spectroscopy revealed chemical states of the constituents Zn, Cr and Se as 2(+), 3(+) and 2(-) respectively. The electrical conductivity and thermo-power measurements in the 300-550 K temperature range showed semiconducting nature of the material and that the electrical conduction is of the n-type. The electrical conductivity is found to be increased continuously up to x = 0.05 and then decreased for further increase in x. The Hall-probe measurements also confirmed n-type conduction. The average Hall coefficient for pure ZnSe is -1.03 x 10(7) cm(3)/C whereas, it is -4.55 x 10(6) cm(3)/C for a sample with x = 0.35.